The Effect of Topical Use of Petroselinum Crispum (Parsley) Versus That of Hydroquinone Cream on Reduction of Epidermal Melasma: A Randomized Clinical Trial. Issue 1 (January 2017) - Khosravan, Shahla; Alami, Ali; Mohammadzadeh-Moghadam, Hossein; Ramezani, Vahide
Abstract : Melasma disfigures the skin and thus influences people's self-image and self-concept. Therefore, melasma influences emotional and psychosocial health in addition to physical health. This clinical trial was performed to assess the effect of the topical use of Petroselinum crispum (parsley) on reduction of the severity of epidermal melasma.